Comparison of Outcome of Renal Transplant with and Without Double J Stenting - Abdul Majeed, Jamshed Rahim, Nadir Hussain, M. Nasir Ibrahim, Jamil Rahim, Hadia Akhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Renal transplant is definitive treatment for chronic renal disease. Renal transplant involves three anastomosis, renal artery, vein and ureter. Some surgeons prefer urinary stenting for prevention of urinary complication like urinary leakage, while others do not. Still there is controversy whether to use or not use intraoperative stenting. The purpose of this study is to share experience of renal transplant with and without stenting. Objective: To compare the outcome of renal transplant with and without intraoperative placement of Double J Stent Study Design: Comparative study. Place and Duration of Study: Department of Urology and Kidney Transplantation, Shaikh Zaid Hospital, Lahore from 1st January 2014 to 31st December 2015. Methodology: One hundred and eight patients with chronic kidney disease had renal transplant. Randomly, 54 patients transplant was done with stenting and in 54 patients transplant was done without stenting. The patients were followed up for presence of urinary leakage. Results: Among 54 renal transplants with stenting, no urinary leakage was found (0%), while in 54 patients without stent placement, urinary leakage was observed in 2 (3.7%) patients. (p=0.153, i.e. >0.05) Conclusion: Ureteric stenting is not mandatory for renal transplantation. Frequency of urinary leakage among patients with renal transplant with stent was low while no leakage was seen with stenting. Difference in rate of urinary leakage with and without stenting was not statistically significant.